Clinical trials on pain lowering effect of ginger: A narrative review. (20th May 2020) - Rondanelli, Mariangela; Fossari, Federica; Vecchio, Viviana; Gasparri, Clara; Peroni, Gabriella; Spadaccini, Daniele; Riva, Antonella; Petrangolini, Giovanna; Iannello, Giancarlo; Nichetti, Mara; Infantino, Vittoria; Perna, Simone
Abstract : Ginger has a pain‐reducing effect and it can modulate pain through various mechanisms: inhibition of prostaglandins via the COX and LOX‐pathways, antioxidant activity, inibition of the transcription factor nf–kB, or acting as agonist of vanilloid nociceptor. This narrative review summarizes the last 10‐year of randomized controlled trials (RCTs), in which ginger was traditionally used as a pain reliever for dysmenorrhea, delayed onset muscle soreness (DOMS), osteoarthritis (AO), chronic low back pain (CLBP), and migraine. Regarding dysmenorrhea, six eligible studies suggest a promising effect of oral ginger. As concerned with DOMS, the four eligible RCTs suggested a reduction of inflammation after oral and topical ginger administration. Regarding knee AO, nine RCTs agree in stating that oral and topical use of ginger seems to be effective against pain, while other did not find significant differences. One RCT considered the use of ginger in migraine and suggested its beneficial activity. Finally, one RCT evaluated the effects of Swedish massage with aromatic ginger oil on CLBP demonstrated a reduction in pain. The use of ginger for its pain lowering effect is safe and promising, even though more studies are needed to create a consensus about the dosage of ginger useful for long‐term therapy.